1998
DOI: 10.18785/grr.1001.01
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Sciaenid (Pisces: Sciaenidae) Larvae in Two Coastal Lagoons of the Gulf of Mexico

Abstract: Stomach contents analyses showed that Leiostomusxanthurus (8.50-12.90 mm SL) had a wide trophic spectrum (15 food categories) with copepods and eggs of invertebrates as main components. In contrast, Micropogonias undulutus (6.65-12.20 mm SL) ingested only six food categories (copepods, eggs of invertebrates, crustacean nauplii, bamacle nauplii, amphipods and other crustaceans). There is an overlap of 73.2 to 83.0% in the diet of these two species. Bairdiella chrysoura (1.17-1.92 mm SL) fed primarily on juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…In addition, fluctuations in density, distribution, and species richness have been observed in the majority of coastal lagoons in response to community dynamics (Aguirre-León et al 2014). This is also the case in this study, as the greater density values were recorded for the larger specimens that were collected in August with the otter trawl (see Table 1), indicating that these species were recruited during the summer after the August spawning, as was observed by Ocaña-Luna and Sánchez-Ramírez (2016). Other factors that may influence the success of a species, and thus its density, include its use of the habitat, its feeding habits, and its geographic distribution.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, fluctuations in density, distribution, and species richness have been observed in the majority of coastal lagoons in response to community dynamics (Aguirre-León et al 2014). This is also the case in this study, as the greater density values were recorded for the larger specimens that were collected in August with the otter trawl (see Table 1), indicating that these species were recruited during the summer after the August spawning, as was observed by Ocaña-Luna and Sánchez-Ramírez (2016). Other factors that may influence the success of a species, and thus its density, include its use of the habitat, its feeding habits, and its geographic distribution.…”
Section: Discussionsupporting
confidence: 80%
“…A review of the literature provided a wide variety of temporal distributions for the species collected in this study. Of the papers consulted, only two coincided with some species/seasons observed here: Ocaña-Luna and Sánchez-Ramírez (2016) recorded Gobiosoma bosc and Diapterus rhombeus in August, Gobionellus oceanicus and Cynoscion arenarius in November and Achirus lineatus both seasons, and Díaz-Ruiz et al (2003) recorded Eucinostomus gula and Orthopristis chrysoptera in August and E. argenteus in December. It is thus nearly impossible to establish patterns, and this reflects the species' freedom of movement in and out of coastal lagoons.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…En la región norte del estado de Veracruz se han desarrollado algunas investigaciones sobre ictioplancton en lagunas costeras: en la laguna de Pueblo Viejo, Sánchez-Ramírez y Ocaña-Luna (2002) estimaron la biomasa en desove de Anchoa mitchilli; en la laguna de Tampamachoco, Ocaña-Luna y Sánchez-Ramírez (1998, 2003 analizaron la alimentación de larvas de esciénidos y la diversidad de larvas de peces, respectivamente; en la laguna de Tamiahua, Flores-Coto, Barba-Torres y Sánchez-Robles (1983) dan a conocer la estructura de la comunidad ictioplanctónica, mientras que Gaspar-Dillanes, Sánchez-Iturbe, González-Yoval y López-García (1995) y Díaz-Ávalos, Barba-Torres y Gaspar-Dillanes (2003) evaluaron la biomasa en desove y los factores ambientales que influyen en la abundancia de A. mitchilli; por otro lado, Sanvicente-Añorve et al (2011) realizaron un estudio sobre la metacomunidad de larvas de peces en lagunas costeras del golfo de México y el Caribe mexicano. Debido a las modificaciones del ambiente y a los pocos trabajos realizados en el sistema, en la presente investigación se analizan la abundancia estacional y la estructura de la comunidad ictioplanctónica a través de un ciclo anual (2011) en la laguna de Tamiahua, posterior al dragado de canales, la rehabilitación y la prolongación de escolleras de la boca de Tampachichi.…”
unclassified
“…Several studies revealed that the diet of fish larvae (Chavance et al, 1984;Ocan˜a-Luna & Sa´nchez-Ramı´rez, 1999) and the major predators in the zooplankton realm, such as cnidarians, ctenophores and chaetognaths (Duro´& Saiz, 2000;Purcel & Arai, 2001) overlap. The diet of larvae in many fish species mainly comprises various life-history stages of copepods, and as fish larvae grow, the prey size and prey diversity increase (Young, 1992).…”
Section: Analysis Of the Relationship Ichthyoplanktonzooplanktonmentioning
confidence: 99%